Engineering and leaching properties of asphalt binders modified with polyurethane and Cecabase additives for warm-mix asphalt application. (30th March 2020) - Awazhar, Nurul Aqilah; Khairuddin, Faridah Hanim; Rahmad, Suzielah; Fadzil, Syazwani Mohd; Omar, Hend Ali; Md. Yusoff, Nur Izzi; Badri, Khairiah Haji
Highlights: The crystalline structure of the binders is unaffected by PU and Cecabase. PU and Cecabase do not have a significant influence on thermal transition of the B-B. The concentrations of all heavy metals leached out are within the standards. Abstract: Asphalt binders have been modified with various additives and modifiers as an effort to fulfil the demand for high-performance pavements. Therefore, this study aims to investigate the engineering and leaching properties of 60/70 penetration grade asphalt binder modified with polyurethane (PU) and Cecabase additives for warm-mix asphalt (WMA) application. Measurements of the physical properties of unmodified and modified asphalt binders were made via penetration, softening point, ductility and viscosity tests. The binder-aggregate adhesivity was established by performing the Vialit test while X-Ray Diffraction (XRD) analysis was conducted to determine crystallinity of the binder. Differential Scanning Calorimetry (DSC) was used to determine thermal behavior of the asphalt binders. Synthetic precipitation leaching procedure (SPLP) test was carried out to determine the mobility of organic and inorganic elements present in the binder. PU as modifier and Cecabase as the WMA additive-enhanced binder stiffness. In contrast to Cecabase, the addition of PU increased viscosity of the binder at varying temperatures. PU also enhanced the interfacial adhesion between the binder and the aggregates. The XRD patterns showed that the incorporation of PU and Cecabase has no influence in the crystalline structure of the asphalt binders. Both PU and Cecabase have the ability to improve the workability of the binder at low temperature. The incorporation PU and Cecabase to the asphalt binder showed insignificant shift of the Tg and Tm . SPLP test results indicated that the amount of heavy metals leached out from the asphalt binder samples have no adverse effect on the environment and also did not exceed the standard for drinking.